THE FACTORS THAT INFLUENCE TIKTOK POPULARITY AS A DIGITAL MARKETING TECHNIQUE TO GROW CUSTOMER ENGAGEMENT - Isna Ayu Safitri Kusuma Dewi; Fibia Sentauri Cahyaningrum; Yusuf Darmawan; Vicky Indarto Setyono (International Journal of Economics, Business and Innovation Research, 2023)
The more widespread use of the internet among the public, a lot of research or surveys have been conducted to understand people's behavior regarding how they interact with the internet. One of the application that is currently widely used is TikTok. TikTok is a social media that is loved by young people as a means of expressing themselves through singing or dancing. The popularity of the TikTok application has grown rapidly since its release because it has very diverse features and can be reached by various age groups. This study aims to determine the effect of informativeness, unique, entertainment, co-creation on the popularity of TikTok using multiple linear regression analysis. The results of the analysis show that these four variables have a significant effect on the popularity of TikTok with a coefficient of determination of 86.2%.